A Review of Nephrotoxicity of Microcystins - Xu, Shuaishuai (Toxins (Basel), 2020)
Cyanobacterial blooms triggered by eutrophication and climate change have become a global public health issue. The toxic metabolites microcystins (MCs) generated by cyanobacteria can accumulate in food chain and contaminate water, thus posing a potential threat to human and animals health. Studies have suggested that aside liver, the kidney may be another target organ of MCs intoxication. Therefore, this review provides various evidences on the nephrotoxicity of MCs. The review concludes that nephrotoxicity of MCs may be related to inhibition of protein phosphatases and excessive production of reactive oxygen species, cytoskeleton disruption, endoplasmic reticulum stress, DNA damage and cell apoptosis. To protect human from MCs toxic consequences, this paper also puts forward some directions for further research.